2013
DOI: 10.1007/s11102-013-0487-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamitis: a diagnostic and therapeutic challenge

Abstract: To report an unusual case of biopsy-proven autoimmune hypophysitis with predominant hypothalamic involvement associated with empty sella, panhypopituitarism, visual disturbances and antipituitary antibodies positivity. We present the history, physical findings, hormonal assay results, imaging, surgical findings and pathology at presentation, together with a 2-year follow-up. A literature review on the hypothalamic involvement of autoimmune hypophysitis with empty sella was performed. A 48-year-old woman presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…In patients with a severe form of primary LH, if the disease is recurrent after surgery or resistant to corticosteroid medications, other therapeutic modalities may be introduced such as immunosuppressive/lympholytic therapy (cyclosporine, methotrexate, azathioprine, or rituximab, a monoclonal antibody against CD20 that selectively induces apoptosis of B lymphocytes) (►Table 2). 13,[22][23][24][25][26][27][28][29][30] In our patient, in the view of the high dose of corticosteroids required to avoid clinical symptoms and the evidence of iatrogenic Cushing's syndrome, the immunosuppressive drug azathioprine was used as an alternative long-term treatment. In the first case describing the use of azathioprine in an aggressive form of LH, after 1 month of azathioprine treatment the suprasellar mass had completely disappeared.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In patients with a severe form of primary LH, if the disease is recurrent after surgery or resistant to corticosteroid medications, other therapeutic modalities may be introduced such as immunosuppressive/lympholytic therapy (cyclosporine, methotrexate, azathioprine, or rituximab, a monoclonal antibody against CD20 that selectively induces apoptosis of B lymphocytes) (►Table 2). 13,[22][23][24][25][26][27][28][29][30] In our patient, in the view of the high dose of corticosteroids required to avoid clinical symptoms and the evidence of iatrogenic Cushing's syndrome, the immunosuppressive drug azathioprine was used as an alternative long-term treatment. In the first case describing the use of azathioprine in an aggressive form of LH, after 1 month of azathioprine treatment the suprasellar mass had completely disappeared.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with refractory disease, various immunosuppressive therapies are used: cyclosporine, methotrexate, azathioprine, or rituximab. 14,[22][23][24][25][26][27][28][29][30] Only a few refractory patients have been treated with stereotactic radiosurgery (SRS). [31][32][33] SRS is a radiation therapy technique that delivers a precise high dose of irradiation (either single-fraction or multi-fraction SRS) to well-defined small to moderate targets.…”
mentioning
confidence: 99%
“…As the disease progresses or subsides, the lesion enlarges or reduces accordingly, occasionally resulting in an ES. 3,7 Cases of AH with secondary ES have also been reported. 14,15 In our series, we suggested that secondary ES (2/5, 40%) could be the consequence of AHT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of antipituitary antibodies has been documented. Imaging confirms pituitary gland inflammation that overextends and compromises the hypothalamus [ 5 , 13 ]; empty Sella can be seen in late stages of the disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second-line treatment options include rituximab, cyclophosphamide [ 14 ], and azathioprine [ 3 , 5 , 6 ] as well as dual-therapy rituximab with cyclophosphamide. Rituximab as monotherapy may be considered second line due to its more favorable side effect profile; it should be considered mainly in critically ill patients or if a patient remains significantly impaired after first-line therapy.…”
Section: Discussionmentioning
confidence: 99%